PENGARUH GAME EDUKASI WORDWALL QUIZ TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS IX UPTD SMP NEGERI 5 GUNUNGSITOLI - Harefa, Vita Hardianti; Harefa, Agnes Renostini; Waruwu, Toroziduhu; Gulo, Hardikupatu (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Learning outcomes serve as a key indicator for measuring changes in students' knowledge and abilities after participating in the learning process. However, the reality at UPTD SMP Negeri 5 Gunungsitoli shows that students' scores in Science are still below the Minimum Completeness Criteria (KKM). This study aims to determine the effect and effectiveness of using the Wordwall Quiz educational game on student learning outcomes in Science. The research method employed was experimental using a Quasi-Experimental Design with a Non-Equivalent Control Group Design. The study population included all ninth-grade students at SMP Negeri 5 Gunungsitoli. The sample consisted of class IX-A as the experimental group (32 students) and class IX-C as the control group (31 students). The research instrument was a learning outcome test, while data analysis was conducted using Microsoft Excel and SPSS version 26. The hypothesis test results, using the Mann-Whitney U Test, showed an Asymptotic Sig. (2-tailed) value of 0.000<0.05, which indicates a significant influence of using the Wordwall Quiz educational game on student learning outcomes. Furthermore, the N-Gain score for the experimental class reached 77.71%, placing it in the